THE EFFECT OF VARIOUS CONCENTRATIONS OF ANTI-ACNE LIQUID SOAP ON THE BACTERIA OF Staphylococcus aureus CAUSES ACNE - Delfi Suganda; Mades Fifendy; Linda Advinda (Jurnal Serambi Biologi, 2022)
his study aims to determine the effect of various concentrations of anti-acne liquid soap on Staphylococcus aureus and the interaction of the two types of liquid soap with their concentrations on the growth of S. aureus bacteria that causes acne. This research is an experimental study using a completely randomized design (CRD) in a 6 x 2 factorial with 3 replications. Factor A is liquid soap for acne, 2 levels are A1 = (Initial: P) , A2 = (Initial: C&C) Factor B is soap concentration, 6 levels are B1 = 2.5% (w/v), B2 = 5 % (w/v), B3 = 7.5% (w/v), B4 = 10% (w/v), B5 = 12.5% ​​(w/v), B6 ​​= Control (sterile distilled water). The results of this study indicate that the effect of various concentrations of anti-acne liquid soap on Staphylococcus aureus bacteria that causes acne is able to inhibit the growth of S. aureus, because the C&C brand of liquid anti-acne soap is able to form an average inhibition zone diameter of 1.94 cm at a concentration of 12, 5% while the anti acne P liquid soap brand was able to form an average inhibition zone diameter of 1.64 cm. From the statistical analysis data using the ANOVA test, the effect of various anti-acne liquid soaps on S.aureus had no significant effect and there was no interaction between the types of anti-acne liquid soap and its concentration on S.aureus which causes acne. Key words anti acne liquid soap, Staphylococcus aureus, concentration